2006
DOI: 10.1097/01.mop.0000193293.87022.4c
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic markers for neonatal sepsis

Abstract: Serial measurements and use of combinations of markers have been reported to improve sensitivity and negative predictive value of these tests. Current markers are not infallible, however, and do not permit neonatologists to withhold antibiotics in sick infants with suspected infection. Thus, many have emerged as useful indicators for early discontinuation of unnecessary antimicrobial therapy. Some infection markers are also useful for identifying infants with severe infection and adverse prognosis. Advances in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
151
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(161 citation statements)
references
References 47 publications
3
151
0
7
Order By: Relevance
“…1 Early warning signs and symptoms of neonatal sepsis are often nonspecific and subtle especially at the onset of infection, and can easily be confused with other common noninfectious causes. 2 The incidence of sepsis ranges from 1 to 10 cases in every 1000 live births, with high mortality rates despite antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1 Early warning signs and symptoms of neonatal sepsis are often nonspecific and subtle especially at the onset of infection, and can easily be confused with other common noninfectious causes. 2 The incidence of sepsis ranges from 1 to 10 cases in every 1000 live births, with high mortality rates despite antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…5 Early diagnosis of LOS in preterm infants may be challenging because of the questionable accuracy and latency of blood culture, and the best single biomarkers, such as C-reactive protein (CRP), procalcitonin (PCT), interleukin (IL)-6, interleukin-8, or their combination has not been identified. [6][7][8][9][10] Therefore, it was recently suggested that additional studies are necessary to identify more accurate biomarkers of neonatal sepsis. 8 Presepsin (P-SEP), or soluble CD14 subtype, is a trunked portion of soluble CD14, which is released by shedding from the surface of various immune cell lines, such as macrophages, monocytes, and neutrophils, after its stimulation by pathogens.…”
mentioning
confidence: 99%
“…Может экспрессироваться на гранулоцитах после активации клеток цитокинами, такими как интерфе-рон-гамма и гранулоцитарный колониестимулирую-щий фактор [31,32]. Наличие CD64 на поверхности нейтрофилов является признаком инфекции и сепсиса [27,33,34]. Метаанализы по клиническому примене-нию данного маркера продемонстрировали уровни его чувствительности и специфичности 85 и 76 % соответ-ственно [35,36].…”
unclassified